A new species of Castianeira Keyserling (Araneae, Corinnidae) from Buenos Aires, Argentina - Rubio, Gonzalo Daniel (2015)
A new species of the spider genus Castianeira (Araneae: Corinnidae) from Argentina, C. coquito, is described on the basis of male and female specimens collected in northeastern Buenos Aires Province and the Ciudad Autónoma de Buenos Aires, Argentina. This new species is characterized by its diminutive size and by the very globose copulatory bulb with a thick neck. It is the sixth species of the genus reported for the country.